In silico study of the impact of the PRKAG2-H401Q mutation on AMPK affinity for AMP and ATP - Souza, Karine Terra de; Dias, Glauber Monteiro; Fernandez, Jorge Hernandez (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2024)
Mutations in the PRKAG2 gene, which encodes the γ2 subunit of AMP-activated protein kinase (AMPK), are linked to a rare cardiomyopathy involving glycogen accumulation, left ventricular hypertrophy, and sudden death. This study investigates a novel His401Gln missense mutation in the PRKAG2 gene and its effects on AMPK γ2 subunit dynamics. Through molecular simulations and free energy analyses, we compared AMP and ATP binding affinities between the wild-type and mutant γ2 subunits. Structural modeling and simulations revealed a significant change in ATP binding at site 3 in the mutant AMPK, suggesting that the His401Gln mutation impacts protein binding behavior. This alteration may contribute to the pathological mechanisms of PRKAG2 cardiomyopathy.